EVALUASI PENGIRIMAN VIDEO MENGGUNAKAN PENGKODEAN SKALABILITAS SPASIAL DENGAN GANGGUAN PADA KANAL INTERNET - Agus Purwadi; Baharuddin Baharuddin (Jurnal Informatika Polinema, 2017)
Video transmission over the internet can be a great possibility of the existence of lost packets (packet loss) and load variations in a large bandwidth. This is a source of network congestion can interfere with the rate of data communication. In this paper the proposed planning optimal error control in scalable video transmission to a video coding technique FGS (Fine Granularity Scalability), which is an improvement on the MPEG-4 video coding, which has outputs are scalable base layer and layer Enhanchement that have different sizes and rates, which the application will be adapted to the transmission network conditions, the ultimate goal is to minimize any distortion from the source to the destination. In the simulation yields a value Peak Signal to Noise Ratio (PSNR) on the base layer of 29, 683 dB and 78,917 dB enhancemenet layer and the base layer for the MSE of 69,998 dB and 0,000834417 dB enhancemenet layer, Means Square Error (MSE) as the performance of the network system performance on video quality for both the base layer and layer Enhanchement.